Strengthening community based natural resources management in the Maasai Mara - Serengeti ecosystem - Lake Victoria Basin Commission (Lake Victoria Basin Commission, 2011)
This consultancy was undertaken by the Kenya Marine and Fisheries Research Institute (KMFRI) for Lake Victoria Basin Commission (LVBC), with a goal of preparing a basis for strenghtening of Community Based Natural Resource Management groups (CBNRM) in the Maasai Mara - Serengeti Ecosystem (MSE). The specific objectives were: to conduct an inventory and SWOT analysis of CBNRM groups; prepare guidelines for engagement of CBNRM groups (in Wildlife Management Areas and Conservancies); and to identify and document for replication CBNRM best practices. The core natural resources considered in this study were in the sectors of forestry, wildlife and water resources. In addition, other natural resources considered were bee keeping, eco-tourism, fisheries, mining and agriculture. Other institutions involved in the consultancy were Maseno University, Kenya Agricultural Research Institute (KARI) and Kenya Forestry Research Institute (KEFRI), all based in Kenya, and Tanzania Wildlife Research Instiute (TWRI) based in Arusha, Tanzania. Methods used in this study involved literature reviews and field surveys carried out from 15th to 21st August 2010 in the MSE. A structured questionnaire was used to obtain primary data. Pre-determined Focus Group Discussion (FGD) question guide with relevant themes and sub-themes was administered to Locally Influencial Persons (LIPs) and key informants. SWOT analysis was conducted on the groups and beneficiaries. Finally, an assessment was carried out on capacities and training gaps of the various groups.An inventory of the CBNRM groups revealed a total of 26 active groups involved in water resources management with 8 groups located in Mara and 18 groups located in Serengeti. With regard to ecotourism groups, a total of 24 active groups were identified within the MSE, with Mara hosting 22 groups and Serengeti having 2 groups. In wildlife conservation, a total of 12 groups were identified with 11 in the Mara and 1 in Serengeti. Forestry sector had 22 groups of which 17 were located in Mara and 5 in Serengeti. Bee keeping had 4 groups which were all based in Mara. Under landuse, there were 9 groups all based in Mara. In the energy sector, there were 3 groups of which 2 were in Mara and 1 in Serengeti. In mining, 2 groups were identified in Mara and 1 group in Serengeti. An analysis of the CBNRM groups revealed that the levels of education for most officials was primary school education (45.8%) or no formal education (8.3%) indicating that traditional systems played a major role in management of natural resources. Results further revealed that CBNRM groups within the MSE faced a wide range of challenges. In forest management the main challenges were limited knowledge (66.7%) and ownership (33.3%). In water resources, poor water quality, inadequate quantity and knowledge on how to improve the management strategy and degradation of catchment areas were cited as the main challenges. In wildlife resources, human-wildlife conflict (54.5%) was the main challenge while fire outbreaks (25%) posed the least threat. The main policy constraints facing the CBNRM groups within the MSE were: that the existing policies on natural resources management were not widely accepted (41.7%); lack of specific policy implementers (21.4%); lack of power to enforce the policies (21.4%); and conflicting policy intentions (46.7%).SWOT analysis on the existing CBNRM groups within the MSE revealed that most groups in the MSE have a legal mandate (87.5% registered) with elaborate constitutions and have a monitoring and evaluation system in place (93.3%). The main weaknesses identified include weak financial base with a heavy dependence on donor funding, inadequate information on key policies, laws, bylaws and regulations. The major opportunities include a diversity of abundant natural resources, available landuse options, rich cultural and social environment, improved collaboration with the government and private sector, improved social security and welfare. There are also opportunities in international conventions and treaties. The main threats are global warming/ climate change, diseases and epidemics competition in resource utilization, conflicting sectoral polices and laws, group sustainability, poverty and environmental degradation. The main capacity building needs within the MSE are sensitization on natural resource management best practices; management skills in book-keeping and preparation of management plans; training in Participatory Rapid Assessment (PRA) techniques; training on livelihood skills and sensitization on policies, laws, legislations and village by-laws.Within the MSE some CBNRM groups manifested best practices in the following areas: benefit sharing with improved socio-eonomic benefits, had governance structures in place, had manifested behavioral change and put measures in place to protect the environment. One of the CBNRM groups which embraced best practices is the Kolong Cultural Village in Mara which had developed programmes in biogas production from cow dung, tree seedling nursery and was also constructing a borehole for water supply besides their ecotourism activities. The second group is Olare – Orok Motorogi Conservancy also in Mara which had taken up projects in making hay-dung briquettes to supply local communities with alternative energy sources. In addition, it had initiated outreach programmes e.g. Koyiaki Guiding School which trains Game Rangers and Tour Guides as well as projects in water, health, roads and bursaries for needy children. Though new, the Mara North Conservancy has initiated programmes that directly benefit the communities, while Olalui Community Forest Association (CFA) and Dupoto have successful projects in tree planting and forest conservation within the Transmara District of Kenya. Within the Serengeti ecosystem, the Ikona WMA practiced good governance with well laid out benefit sharing mechanisms and equity. Robanda Joint Venture Association manages village land through a committee with a wide range of benefits to the community. Finally, the Kikundi cha walezi watoto yatima na mazingira magumu, Kinesi-Serengeti embraced issues of environmental management through use of solar jikos, organic farming, fish farming and brick making using local materials without use of wood for curing by drying the bricks in the sun besides their normal programme of tree planting The formation process and functions of a trans-boundary NRM committee is proposed, taking into consideration variation of policies and approaches especially in wildlife management. This study proposes the formation of a CBNRM network for conservancies and WMAs. The network will tackle transboundary issues related to wildlife e.g poaching, migration of wildlife, management regimes and fires. Transboundary guidelines for engagement of WMAs and Conservancies have been prepared and entail the guiding principles of CBNRMs such as benefit sharing arrangements, the size of group that can better manage the resource and the decision making process The main recommendations from this study for strengthening existing CBNRM groups are: • Support CBNRM groups in creating networks at trans-boundary level on NRM issues to enhance sharing of information and experiences on best practices. • Carry out training/clinic workshops for CBNRM groups to improve their skills on good management practices including financial and administrative management, conflict resolution mechanism, entrepreneurship, negotiation skills, fund raising and benefit sharing. • Conduct sensitization sessions to raise awareness on the significance of environmental conservation and sustainable resource utilization. • Explore best practices from successful stories, locally, regionally and intenationally through study tours. • Sensitize CBNRM groups on the principles and importance of cost sharing (needs and advantages) through the contribution of more resources (cash and in kind) to various services (e.g. monitoring and enforcement) that are essential for the long term sustainability of natural resource management efforts.
Keywords: Ecosystems; Natural Resources Management; Community Based Conservation